Supervisi Pendidikan di Sekolah Inklusif: Tantangan dan Solusinya - Muhammad Iqbal; Fadila, Az Zahra Nur; Selsha Amalia; Suci Julianti Nasution (Indo-MathEdu Intellectuals Journal, 2024)
Educational supervision in inclusive schools faces various challenges, particularly in addressing the diverse needs of students, the lack of specialized training for teachers, and the limitations of resources and supporting facilities. The aim of this research is to identify the challenges of supervision in inclusive schools and to seek effective solutions to improve the quality of supervision within the context of inclusive education. This study employs a library research method, using data sources from books, journals, and relevant previous studies. Data analysis is conducted qualitatively through literature review. The findings indicate that enhancing teacher competency through continuous training, implementing collaborative supervision methods, and strengthening supporting facilities are effective solutions to address the challenges of supervision in inclusive schools. In conclusion, educational supervision in inclusive schools can operate more optimally when supported by a comprehensive approach, both in terms of teacher competency development and the provision of adequate facilities